Pectin nanoemulsions in multiple emulsions: Stability and encapsulation efficiency. (January 2021) - Massel, V.; Fang, Y.; Corredig, M.
Graphical abstract: Highlights: In situ gelation of pectin created nanocapsules in the inner phase. Multiple emulsions with gelled nanocapsules required less emulsifier. Magnesium and brilliant blue release was not affected by the gelled inner phase. Abstract: Pectin nanocapsules were obtained by gelling the inner droplets, in situ, in a multiple emulsion of the water in oil in water (W/O/W) type, using the enzyme Pectin methyl esterase. The inner phase was tested for its encapsulation efficiency by addition of brilliant blue or magnesium chloride. Rheological measurements and light scattering showed similarities for gelled and non gelled droplets containing high methoxy pectin. After one month of storage, the gelled nanocapsules showed a population of larger droplets, not appearing in the other W/O/W emulsions: the non gelled pectin droplets or control with no pectin. Confocal microscopy observations demonstrated the presence of the inner water droplets in all emulsions after one month of storage at 4 °C. Brilliant blue was retained in the inner droplets containing pectin, and the retention was not affected by the gelled inner phase. Magnesium ions were retained in all treatments, even in the case of control W/O/W emulsions, not containing pectin. With both systems studied, the presence of gelled nanocapsules did not cause significant differences in the encapsulation efficiency or stability of the W/O/W emulsions.